CHALLENGING SOCIAL STANDARDS THE BLACK AESTHETICS IN TONI MORRISON’S THE BLUEST EYE - Alanazi, Meshari S. (Linguistics and Culture Review, 2021)
Prior to the evolution of the Black Arts Movement, the concept of “beauty” in the United States relied on specific standards, among which were being white and having blue eyes. However, this narrow definition changed over time as sociopolitical factors affected such concepts. Therefore, it is not surprising that the Black Arts Movement affected and changed the concept of beauty among Black Americans. African Americans stood not against white individuals but against everything that was unjust toward them in white American society. As a result, the literary works created by Black writers had to be built on either a political or an aesthetic framework. This paper examines the standards of beauty in The Bluest Eye and discusses the novel’s ideological tone and its references to the Blues, Black aesthetics and Black feminism. The novel was published in the middle of the Black Arts Movement era, and it satisfies the Black Art Movement’s major concern, which is how the work of art can help African Americans live a better life. Morrison’s novel highlights the concept of beauty at the time and how to change it among Black Americans.